Spatial Distribution of Immune Cells in Head and Neck Squamous Cell Carcinomas - Idel, Christian; Ribbat-Idel, Julika; Klapper, Luise; Krupar, Rosemarie; Bruchhage, Karl-Ludwig; Dreyer, Eva; Rades, Dirk; Polasky, Christina; Offermann, Anne; Kirfel, Jutta; Perner, Sven; Wollenberg, Barbara (Frontiers in Oncology, 2021)
Background: Head and Neck Squamous Cell Cancers (HNSCC) have a very moderate response rate to immune checkpoint inhibitors (ICI) treatment compared to other cancer types. Lacking predictive markers for treatment response, we analyzed the immune status of HNSCC and assessed the spatial distribution of immune cells. Materials and Methods: Via assessing H&E staining, we divided HNSCC by the immune cell distribution in hot, cold, and excluded tumors. For each group, we performed serial immunohistochemical (IHC) stainings of immune cell markers, checkpoint molecules, and immune regulators. Results: The spatial distribution was different for each immune cell type, allocating T reg and CD11b cells predominantly in the stroma. CD4 and CD8 cells were present either in the tumor stroma or between cancer cells. Interestingly, the PD-1 and PD-L1 expression were higher in hot tumors in comparison to cold and excluded tumors. p-SMAD expression (indicating active TGF-β) was higher in excluded tumors. Conclusion: Different immune cell distribution patterns within tumors might be crucial for ICI treatment response since hot tumors have the highest expression of PD-1 and PD-L1. TGF-β might be a key regulator for immune cell distribution and a promising therapeutic target that determines the formation of hot or excluded immune patterns.